Cooperation is in our nature: Nature exposure may promote cooperative and environmentally sustainable behavior. (June 2015) - Zelenski, John M.; Dopko, Raelyne L.; Capaldi, Colin A.
Abstract: Theory and correlational research suggest that connecting with nature may facilitate prosocial and environmentally sustainable behaviors. In three studies we test causal direction with experimental manipulations of nature exposure and laboratory analogs of cooperative and sustainable behavior. Participants who watched a nature video harvested more cooperatively and sustainably in a fishing-themed commons dilemma, compared to participants who watched an architectural video (Study 1 and 2) or geometric shapes with an audio podcast about writing (Study 2). The effects were not due to mood, and this was corroborated in Study 3 where pleasantness and nature content were manipulated independently in a 2 × 2 design. Participants exposed to nature videos responded more cooperatively on a measure of social value orientation and indicated greater willingness to engage in environmentally sustainable behaviors. Collectively, results suggest that exposure to nature may increase cooperation, and, when considering environmental problems as social dilemmas, sustainable intentions and behavior. Highlights: We tested the effects of viewing brief videos containing natural vs. built spaces. Nature produced more cooperative and sustainable behavior in commons dilemmas. Nature produced higher social value orientation scores and sustainability intentions. Nature's effects on cooperation and sustainability were independent of mood.